Influence of vintage and grape maturity on volatile composition and foaming properties of sparkling wine from Savvatiano (Vitis vinifera L.) variety - Dimitrios Miliordos; Nikolaos Kontoudakis; Aggeliki Kouki; Alexandros Kanapitsas; Despina Lola; Elli Goulioti; Yorgos Kotseridis (OENO One)
The timing of grape harvest is critical in the winemaking process of sparkling wines. It is essential for grapes to have the right amount of sugars and the optimum amount of sugars and level of acidity perfect level of acidity as they ripen. This is crucial not just for achieving the desired alcohol content in the wine but also for ensuring the production of the aromatic precursors. The chemical composition of sparkling wines is closely linked to the quality of their foam. The goal of this study was to determine how different levels of grape maturity impact the chemical and sensory properties of Savvatiano sparkling wines after 15 months maturation in the bottle. Grape ripening stage was found to have a significant influence on the content, composition and development of organic acids and volatile compounds in the wine, and on its sensorial attributes. In the resulting Savvatiano sparkling wines produced by a single grape variety, those produced from grapes at the earliest stage of maturity exhibited higher levels of terpenes, organic acids and foam characteristics. This was reflected in the sensory evaluation, these wines scoring the highest for descriptors like “floral”, “green apple” and “foam intensity”. This study represents the first analysis of the chemical composition and sensory traits of white sparkling wine made from the indigenous grape variety Savvatiano. By applying a comprehensive approach that examines both wine metabolites and sensory attributes, it is possible to determine the ideal harvest time for producing high quality Savvatiano sparkling wines.